Implementasi Supervisi Akademik dalam Meningkatkan Kualitas Pembelajaran di SMKN 4 Tanah Grogot - Adiyono Adiyono; Andreas Rudy Lesmana; Derizky Anggita; Rahmani Rahmani (Journal on Education, 2023)
The purpose of this study was to find out how the mechanism for implementing supervision activities at SMKN 4 Tanah Grogot is. This study used a qualitative method with library sources and interview techniques with Mr. Capsule Anwar S.P as the principal of SMKN 4 Tanah Grogot. The results of the study indicate that the implementation of supervision at SMKN 4 has been carried out properly according to existing procedures. The supervising actors are the school principal and his deputy as well as the heads of the departments of each department. The main purpose of supervision is to assist teachers in developing the techniques and methods they use when teaching. Supervisor implementation at SMKN 4 Tanah Grogot has been carried out as well as possible. Supervision of the program well, as well as its implementation. The purpose of supervising is to improve the quality of learning for teachers and improve/improve the methods teachers use when teaching, the point is that there are changes in a better direction in the future for supervised teachers.